High tibial osteotomy: A review of the readability and quality of patientinformation on the internet - Matthew Clark; Ian Colin Baxter; Matthew Hampton; Robert D Sandler; Andrew Legg (Health Promotion Perspectives, 2021)
Background: High tibial osteotomy (HTO) is a common procedure performed for unicompartmental knee osteoarthritis (OA). Patients are increasingly using the internet to research surgical procedures to help aid decision making. Our aim was to assess the readability and quality of information available to patients online relating to HTO. Methods: A systematic review of three search engines Google, Bing, and Yahoo using the search terms "high tibial osteotomy" and "tibial osteotomy" separately was performed. The first three pages of results for each search engine were analyzed. Readability was assessed using the Flesch Reading Ease Scale (FRES), Flesch-Kincaid Grade level (FKGL) and the Simple Measure of Gobbledygook formula (SMOG). Quality was assessed with the DISCERN questionnaire, JAMAbenchmarks and the presence of Health on the Net Foundation Code of Conduct (HONCode). Results: Twenty-four webpages were included after duplicates (n=42) and exclusions (n=24).The overall readability was low, with a mean FRES of 53.2 (SD: 9.1), FKGL 10.7 (SD: 1.8),SMOG 10.4 (SD: 1.5). Quality was also low with a mean DISCERN score of 42 (SD: 12.3).None of the webpages fulfilled all of the JAMA benchmarking criteria and only 2/24 (8.3%)webpages possessed HONCode certification. Conclusion: The overall online information available to patient’s considering HTO is of lowreadability and quality. Improving the quality and readability of patient information online willbenefit informed patient decision making before HTO surgery.